2020
DOI: 10.1007/s11886-020-01314-0
|View full text |Cite
|
Sign up to set email alerts
|

Disorders of the Aorta and Aortic Valve in Connective Tissue Diseases

Abstract: Purpose of Review The incidence of aortic valve disease in inherited connective tissue disorders is well documented; however, recent studies have only begun to unravel the pathology behind this association. In this review, we aim to describe the etiology, clinical manifestations, management, and prognosis of aortic and aortic valvular disorders that co-exist in a variety of connective tissue diseases. An extensive literature review was performed in PubMed. Articles from 2008 to 2018 were included for review. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 76 publications
0
16
0
1
Order By: Relevance
“…13 Studies have demonstrated a possible role for VHD as a predictive factor for the severity of AS. 11,12 The presence of VHD is related to the duration of AS and predicate for peripheral joint involvement. 14,15 The association between AS and VHD raises interesting and important issues since valve involvement is a potential risk for heart failure or even death.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Studies have demonstrated a possible role for VHD as a predictive factor for the severity of AS. 11,12 The presence of VHD is related to the duration of AS and predicate for peripheral joint involvement. 14,15 The association between AS and VHD raises interesting and important issues since valve involvement is a potential risk for heart failure or even death.…”
Section: Introductionmentioning
confidence: 99%
“…4 Grygiel-Górniak et al . 11 reported that approximately 80% of patients with AS have aortic valve and/or aortic root involvement. 12 Overall, aortic regurgitation is the most frequently reported VHD in patients with AS.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have described only case reports of severe aortic valve stenosis requiring aortic valve replacement in patients with SSc, with only three case reports in the last decade. 15 In 2019, contrary to prior literature, Butt et al 16 demonstrated an increased risk of AS in patients with scleroderma as compared to matched controls in addition to numerous other cardiac manifestations. This retrospective cohort study utilizing the Danish healthcare registers reported an incidence rate of AS to be 0.29 per 100 person years as compared to 0.10 in their matched controls with HR (2.99; 95% CI: 2.25-3.97) among patients with scleroderma.…”
Section: Discussionmentioning
confidence: 93%
“…Histopathological findings of the affected aortic valve, root and sinuses include fibrous tissue deposition in the adventitia and intima resulting from platelet aggregation and fibroblast activation ( 23 ). It is thought that inflammation and subsequent dilatation of the aortic root in ankylosing spondylitis eventually lead to fibrotic thickening and shortening (i.e., inward rolling) of the aortic cusps and increased aortic stiffness ( 24 , 25 ).…”
Section: Ankylosing Spondylitismentioning
confidence: 99%